Relationship between photosynthetic performance and yield loss in winter oilseed rape (Brassica napus L.) under frost conditions - Dąbrowski, P; Jełowicki, Ł; Jaszczuk, Z M; Maihoub, S; Wróbel, J; Kalaji, H M (Photosynthetica, 2024)
Winter oilseed rape (Brassica napus L.), the principal oilseed crop in Europe, is notably vulnerable to spring frosts that can drastically reduce yields in ways that are challenging to predict with standard techniques. Our research focused on evaluating the efficacy of photosynthetic efficiency analysis in this crop and identifying specific chlorophyll fluorescence parameters severely impacted by frost, which could serve as noninvasive biomarkers for yield decline. The experiments were carried out in semi-controlled conditions with several treatments: a control, one day at -3°C, three days at -3°C, one day at -6°C, and three days at -6°C. We employed continuous-excitation and pulse-amplitude-modulation chlorophyll fluorescence measurements to assess plant sensitivity to frost. Also, plant gas exchange and chlorophyll content index measurements were performed. Certain parameters strongly correlated with final yield losses, thereby establishing a basis for developing new agricultural protocols to predict and mitigate frost damage in rapeseed crops accurately.
Keywords: plant traits; abiotic stresses; chlorophyll a fluorescence; bioindicator; plant gas exchange; noninvasive biomarkers